2012
DOI: 10.1049/iet-its.2011.0130
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent intersection support for powered two-wheeled riders: a human factors perspective

Abstract: Given that intersections represent particularly hazardous situations for riders of powered two wheelers, an intelligent intersection support system has been developed. This system provides a warning whenever the rider approaches an intersection at an unsafe speed. This study reports the results of a pilot evaluation of the system from a human factors perspective. In a motorcycle simulator, the system was tested with two alternative rider interfaces: a force feedback throttle and a haptic glove. Riding with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The raw data was logged to comma separated value (CSV) files. The software incorporates visual displays of the tactile sensors; the amount force of each hand activity is indicated with color and any emergent event is indicated with sound alarms [6]. In this research, raw data sampling was initially performed at 20 Hz, as generally suggested sampling frequency in other similar works [5, 13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The raw data was logged to comma separated value (CSV) files. The software incorporates visual displays of the tactile sensors; the amount force of each hand activity is indicated with color and any emergent event is indicated with sound alarms [6]. In this research, raw data sampling was initially performed at 20 Hz, as generally suggested sampling frequency in other similar works [5, 13].…”
Section: Methodsmentioning
confidence: 99%
“…Measurement in more natural environments would increase the efficiency of various interventions [5]. Though different types of force transducers exist, tactile sensors are thin, lightweight, and flexible, making them ideal for integration into human wearable technology, which have been reported as being more efficient and user friendly in applications [6]. Tactile sensors placed on the fingertips of gloves for measuring surface hardness and pressure can be used to sense finger position [7] and recognize different objects [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies [1][2][3][4][5] have identified motorcycle right-of-way (ROW) crash as the most typical and catastrophic carmotorcycle crash that occurs at an intersection. The crash type involves a car maneuvering into the path of an approaching motorcycle, primarily due to motorcycle's poor conspicuity or car driver's speed/distance judgment error.…”
Section: Introductionmentioning
confidence: 99%
“…During the past years motorcycle simulators were developed in order to investigate aspects of motorcycle rider interaction [6][7][8]. These types of motorcycle simulators are mostly used to assess human factors related topics such as hazard perception [9,10] or concepts of human-machine interfaces (HMIs) [11,12]. As the methodology of riding simulation enables testing in a safe and controlled environment, it was chosen to approach the workload assessment for motorcycle riders.…”
Section: Introductionmentioning
confidence: 99%